2015
DOI: 10.2174/1874350101508010044
|View full text |Cite
|
Sign up to set email alerts
|

Internet Access at Home and its Relationship to Well-being in Deprived Areas of London

Abstract: Purpose:The existing studies of the association between Internet usage and well-being have produced contradictory results. This study explores the associations between Internet access at home and well-being, as well as other lifestyle variables. Design/methodology/approach: The study was done in a probability sample of 800 community-dwelling adults aged 16 and over in six most deprived areas of the Redbridge borough of London. Using face-to-face interviews, information on the demographics, lifestyle, Internet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
(49 reference statements)
2
4
0
Order By: Relevance
“…There were particularly low rates of internet access by those who were older, retired, lacking educational qualifications, and with a long-standing illness or disability, and relatively high rates of home internet use by those with children, those in work or full-time education and non-British citizens. These patterns are similar to those reported previously in a study of deprived areas of London [47], with our finding for non-British citizens echoing the earlier finding that internet access was higher among more recent migrants, perhaps due to the need to keep in contact with relatives abroad in the earlier stages of migration and settlement.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…There were particularly low rates of internet access by those who were older, retired, lacking educational qualifications, and with a long-standing illness or disability, and relatively high rates of home internet use by those with children, those in work or full-time education and non-British citizens. These patterns are similar to those reported previously in a study of deprived areas of London [47], with our finding for non-British citizens echoing the earlier finding that internet access was higher among more recent migrants, perhaps due to the need to keep in contact with relatives abroad in the earlier stages of migration and settlement.…”
Section: Discussionsupporting
confidence: 92%
“…We observed a number of social gains associated with the use of the internet among our respondents, particularly for those accessing the internet both via a mobile phone and elsewhere, including a higher likelihood of regular contact with relatives, friends and neighbours and a higher likelihood of available financial support (also true for those who only accessed the internet via a mobile phone). The finding on financial support was also reported in deprived communities in London, though the finding on neighbour contact elaborates on the earlier study, which reported that social ties mediated the relationship between internet access and wellbeing, though without separately reporting on neighbour contacts [47]. We did not find any consistent negative associations of internet access with social effects among our participants.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations